Caffeine use or napping to enhance repeated sprint performance after partial sleep deprivation: Why not both? - Romdhani, M.; Souissi, N.; Moussa-Chamari, I.; Chaabouni, Y.; Mahdouani, K.; Sahnoun, Z.; Driss, T.; Chamari, K.; Hammouda, O. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the effect of a 20-minute nap opportunity (N20), a moderate dose of caffeine (CAF; 5 mg·kg-1), or a moderate dose of caffeine before N20 (CAF+N) as possible countermeasures to the decreased performance and the partial sleep deprivation-induced muscle damage.